Covalent co-assembly between resilin-like polypeptide and peptide amphiphile into hydrogels with controlled nanostructure and improved mechanical properties. (3rd December 2019) - Okesola, Babatunde O.; Lau, Hang K.; Derkus, Burak; Boccorh, Delali K.; Wu, Yuanhao; Wark, Alastair W.; Kiick, Kristi L.; Mata, Alvaro
Abstract : Covalent co-assembly holds great promise for the fabrication of hydrogels with controllable nanostructure, versatile chemical composition, and enhanced mechanical properties given its relative simplicity, high efficiency, and bond stability. Abstract : Covalent co-assembly holds great promise for the fabrication of hydrogels with controllable nanostructure, versatile chemical composition, and enhanced mechanical properties given its relative simplicity, high efficiency, and bond stability. This report describes our approach to designing functional multicomponent hydrogels based on photo-induced chemical interactions between an acrylamide-functionalized resilin-like polypeptide (RLP) and a peptide amphiphile (PA). Circular dichroism (CD) spectroscopy, electron microscopy, and amplitude sweep rheology were used to demonstrate that the co-assembled hydrogel systems acquired distinct structural conformations, tunable nanostructures, and enhanced elasticity in a PA concentration-dependent manner. We envisage the use of these materials in numerous biomedical applications such as controlled drug release systems, microfluidic devices, and scaffolds for tissue engineering.